Teknik pembenihan ikan Lele mutiara (Clarias gariepinus) di Unit Pembenihan Rakyat SD. Mina Jaya - Khairunnisa, Surya; Handayani, Rizky; Putri Bb, Mutia S.; Fadli, Muhammad; Surya, Muhammad; Layla, Khairani (Universitas Sam Ratulangi, 2023)
Abstract Pearl catfish is a freshwater fish that has enormous potential because this fish is able to increase growth by 100-150% and 150-200%. Pearl catfish can be developed in cultivation to replace other types of catfish. The aim of this research is to find out the techniques for hatching pearly catfish (Clarias gariepinus) in the Mina Jaya Elementary School People's Hatchery Unit, Kongsianam Village, Asahan Regency. Data was collected through observation and interview methods. The research method used was the observation method carried out by collecting data directly in the field and playing an active role in the cultivation of pearl catfish (C. gariepinus) spawning. Meanwhile, the interview method was carried out by collecting data obtained from the owner of the Mina Jaya Elementary School People's Seeding Unit. Based on research results, natural spawning of catfish with a female weight of 1.1 kg results in high fecundity, fetilization rate and heaching rate. The resulting fecundity value was 75,000 eggs, the resulting FR value was 83%, and the resulting HR value was 79%. The value resulting from natural spawning was relatively high and the results were good. The high degree of egg hatching was influenced by egg quality, air quality, and how to handle the hatching period. Keywords: spawning, reproduction, broodstock, hatching rate